Pengaruh Model Pembelajaran Cotextual Teaching And Learning(CTL) Berbantuan Pop Up Book Terhadap Pemahaman Konsep Peserta Didik Pada Mata Pelajaran IPA Kelas III Sekolah Dasar - Fitria Khairunnisa; Guntur Cahaya Kesuma; Hasan Sastra Negara (Yayasan Azhar Amanaa Yogyakarta, 2026)
The low conceptual understanding of third-grade elementary students in science learning remains a critical issue because instruction is still often teacher-centered and lacks concrete learning media. This study aimed to examine the effect of the Contextual Teaching and Learning(CTL) model supported by Pop Up Book media on students’ conceptual understanding in science learning at MI Al-Islamiyah Kotabumi. This research employed a quantitative approach using a quasi-experimental method with a Non-Equivalent Control Group Design. The sample consisted of 45 students, including 23 students in the experimental class and 22 students in the control class. Data were collected through pretest and posttest and analyzed using normality test, homogeneity test, N-Gain, Independent Samples t-Test, and effect size. The results showed that the experimental class obtained a posttest mean score of 17.70, higher than the control class mean score of 11.67. The N-Gain score of the experimental class was 0.77, categorized as high, while the control class obtained 0.01, categorized as low. The t-test result showed a significance value of 0.000 < 0.05, with Cohen’s d of 4.31. Therefore, CTL supported by Pop Up Book had a significant and strong effect on students’ conceptual understanding in science learning. The implication is that teachers can use this model as an alternative strategy to create concrete, active, and contextual science learning.